Development Strategy for Pulagan Tampaksiring Nature Tourism as a Tourist Attraction in Gianyar Regency, Indonesia - Ni Made Darmini; L. K. Herindiyah Kartika Yuni; I Wayan Kartimin (Tourism and Hospitality Insights, 2025)
Introduction: Pulagan Tampaksiring, located in Gianyar Regency, Indonesia possesses significant potential as a natural tourist attraction. However, the site still faces various limitations, including underdeveloped infrastructure and a lack of essential supporting facilities such as sanitation, electricity, ticketing counters, and designated parking areas. These shortcomings hinder the optimal development of the destination. This study aims to explore the tourism potential of Pulagan Tampaksiring, identify the challenges faced in its development, and propose appropriate strategies to enhance its role as a natural tourist attraction. Methods: This research employs a qualitative descriptive approach. Data collection was conducted through in-depth interviews, direct observation, and documentation. The research subjects include tourism stakeholders involved in the management and development of the Pulagan Tampaksiring natural tourism site. Results: The findings indicate that: (1) Pulagan Tampaksiring has considerable natural, cultural, and spatial potential to be developed as a nature-based tourist attraction; (2) the main challenges include the lack of adequate infrastructure, limited stakeholder coordination, and minimal promotion efforts; and (3) development strategies that can be implemented involve strengthening cooperation among stakeholders, improving supporting facilities, and increasing promotional activities to raise awareness and interest among tourists. Conclusion: Pulagan Tampaksiring holds strong potential to become a leading natural tourism destination in Gianyar Regency. However, to realize this potential, integrated development strategies must be adopted, focusing on infrastructure improvement, institutional collaboration, and promotional enhancements. These efforts are essential to ensure sustainable and competitive tourism development in the region.